The Role of Sociodemographic and Territorial Factors in Influencing the Subjective Quality of Life. First Results Based on the Italian Panel Survey ITA.LI - Bottini, Luca (Italian Sociological Review, 2025)
The topic of quality of life (QOL) is one of the most important fields of study in social science since decades. Although various branches of the social sciences have addressed this topic, sociology undoubtedly represents a particularly relevant field for this inquiry. Specifically, this article aims to valorize the role played by sociodemographic and territorial variable in influencing subjective quality of life (Subj-QOL). The theoretical framework of Subj-QOL chosen for this article is rooted in three pivotal dimensions: the material well-being, the residential satisfaction and the psychological well-being. Even though the concept of QOL potentially spans to several domains and sub-concepts, a more focused approach has been followed by selecting the most important conceptual areas of an individual’s subjective well-being. The analysis of objective QOL, in fact, should go hand in hand with Subj-QOL in order to lead the activity of policy making and decision-making processes. This article presents the results of a first outlook to the data coming from a recently established longitudinal study on social transformations based in Italy (ITA.LI). The study relies on data from the first wave of the survey and, therefore, does not adopt a longitudinal approach but rather a cross-sectional one. On the one hand, the objective is to identify groups within the Italian population that represent different types of Subj-QOL; on the other hand, it aims to assess the role of sociodemographic and territorial variables in determining the likelihood of belonging to each specific group.